Penggunaan Media Gambar Seri Untuk Meningkatkan Kemampuan Berbicara Anak Usia Dini - Iis Aprinawati (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2017)
One of the characteristics of early childhood is to have a strong sense of enthusiasm and curiosity towards many things around it. Curiosity can be raised using the media. Media is a means of learning that can bring the interest of students to learn because the media is everything that can be used to channel the message, stimulate the mind, attention, and willingness of students to be involved in the learning process. The series image media has a sequence of images that can stimulate the child's mind to speak and produce a continuous story. The purpose of the study explains the media of this series can increase the students' interest to speak so that the ability to speak early child is increasing. The research method used in this study is literature review is a series of activities related to the method of collecting data library, reading and recording and managing research materials. Research results obtained by using a series of drawing media can develop the potential for child speech development and increase vocabulary mastery.